2018
DOI: 10.18805/ijar.b-3229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding graded levels of apple pomace on growth performance, haemato-biochemical parameters and rumen metabolites in crossbred calves

Abstract: To study effect of feeding graded levels of apple pomace on performance of crossbred calves,90 days growth trial followed by 6 days metabolic trail was conducted on 16 female Jersey crossbred calves divided into four equal groups with control (T0) fed concentrate diet without apple pomace and experimental groups viz, T1, T2 and T3, where maize was replaced by 25%, 50% and 75% of apple pomace, respectively. There was no significant difference in dry matter intake, growth performance, feed conversion ratio and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…But another study showed that supplementing 0.29% methionine and 2.27% lysine of dry matter, respectively, had no effect on rumen fermentation of late-lactation cows (Chung et al, 2006); it is also reported that supplementing free-form methionine (0.77% of dry matter) and lysine (0.91% of dry matter) had no effect on ruminal NH 3 -N compared with control (Sun et al 2007); Therefore, the influence of oral supplementation of free methionine and Lysine-HCl on rumen fermentation parameters seems unpredic Table. Chemical compositions of longissimus dorsi muscle: In our study, the chemical composition of the longissimus dorsi muscle including AAs fraction, umami AAs content, essential AAs content and total AA (Table 4) were not different significantly (P0.05) among treatments. The chemical composition always depicts the potential feeding value of a feedstuff (Massod et al 2018). Amino acids (AAs) are the fundamental units of protein, and AAs contents play an important role in meat quality by providing nutritive value and flavor characteristics (Cai et al, 2010); Previous study reported that AAs supplementation will affect the amino acids content of muscle in monogastric animal, for example, the total sulfur amino acids supply in pigs diet affected the amino acid composition of protein in all tissues, but the methionine content changed only in the liver (Conde-Aguilera et al, 2014).…”
Section: Rumen Fermentation Parametersmentioning
confidence: 99%
“…But another study showed that supplementing 0.29% methionine and 2.27% lysine of dry matter, respectively, had no effect on rumen fermentation of late-lactation cows (Chung et al, 2006); it is also reported that supplementing free-form methionine (0.77% of dry matter) and lysine (0.91% of dry matter) had no effect on ruminal NH 3 -N compared with control (Sun et al 2007); Therefore, the influence of oral supplementation of free methionine and Lysine-HCl on rumen fermentation parameters seems unpredic Table. Chemical compositions of longissimus dorsi muscle: In our study, the chemical composition of the longissimus dorsi muscle including AAs fraction, umami AAs content, essential AAs content and total AA (Table 4) were not different significantly (P0.05) among treatments. The chemical composition always depicts the potential feeding value of a feedstuff (Massod et al 2018). Amino acids (AAs) are the fundamental units of protein, and AAs contents play an important role in meat quality by providing nutritive value and flavor characteristics (Cai et al, 2010); Previous study reported that AAs supplementation will affect the amino acids content of muscle in monogastric animal, for example, the total sulfur amino acids supply in pigs diet affected the amino acid composition of protein in all tissues, but the methionine content changed only in the liver (Conde-Aguilera et al, 2014).…”
Section: Rumen Fermentation Parametersmentioning
confidence: 99%
“…Several studies have demonstrated its potential as a substitute for conventional feed, showing no adverse effects on growth performance. For instance, Massod et al ( 2 ) fed crossbred calves varying amounts of apple residue as a substitute for corn, observing no significant differences in growth performance or nutrient digestibility. Similarly, Sharif et al ( 3 ) found that feeding orange pulp to lambs did not affect their feed intake or growth performance negatively.…”
Section: Introductionmentioning
confidence: 99%
“…pomace (Ajila et al, 2015). Various pomace sources from the food industry have been used as alternative feed additives for animal diets (Sirilaophaisan et al, 2015;Vichasilp et al, 2017;Massod et al, 2018) and if correctly treated, these waste materials can be beneficial for both diets and animals. These feedstuffs are relatively cheap, they are waste-products, they create disposal issues for the fruit industry and typically, they are locally available (Mandey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%